1989
DOI: 10.1364/ol.14.000227
|View full text |Cite
|
Sign up to set email alerts
|

Asymptotic evolution of transient pulses undergoing stimulated Raman scattering

Abstract: Propagation of short, transient pulses undergoing stimulated Raman scattering over long length scales is considered. It is shown that under common experimental circumstances the evolution has two different regimes: an I regime, at short lengths, where the pump changes little and the Stokes rapidly grows, and a J regime, at long lengths, where the Stokes intensity is close to saturation and the pump intensity decreases slowly as the square root of distance. The distance at which the J regime is reached is deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1990
1990
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Previous work tuned the gas pressure and pump energy. Meng et al (2017) also recently showed RDW emission from an OPA tuned between 1.3 and 1.5 μm in an Ar-filled broadband-guiding HC-PCF. As the pump wavelength in this case was much closer to the zero dispersion wavelength, the RDW emission was shifted to around 1000 nm.…”
Section: Infrared Pumping For Rdw Emissionmentioning
confidence: 80%
See 1 more Smart Citation
“…Previous work tuned the gas pressure and pump energy. Meng et al (2017) also recently showed RDW emission from an OPA tuned between 1.3 and 1.5 μm in an Ar-filled broadband-guiding HC-PCF. As the pump wavelength in this case was much closer to the zero dispersion wavelength, the RDW emission was shifted to around 1000 nm.…”
Section: Infrared Pumping For Rdw Emissionmentioning
confidence: 80%
“…Accordions are the nonsolitonic solutions of the sine-Gordon equation associated with TSRS. In the presence of memory they dominate the long-distance evolution of the system instead of solitons (Menyuk and Hilfer, 1989;Menyuk, Levi, and Winternitz, 1992;Menyuk, 1993). Two difficulties severely hampered the previous attempts for observing accordions in free-space interaction geometry, namely, designing an experiment of sufficient length to observe the phenomenon, while avoiding the parasitic interference from the higher-order Raman sidebands (Duncan et al, 1988).…”
Section: Early Developments Of Coherent Raman Effects In Hc-pcfsmentioning
confidence: 99%
“…While soliton solutions exist, they are always transient [20,21]. Numerical results [22,23] indicate that the evolution passes through three regimes: (1) an I regime in which the Stokes amplitude is small compared to the pump amplitude and grows exponentially, (2) a transition regime in which the Stokes and pump amplitudes are comparable, and (3) a J regime in which the pump amplitude is small compared to the Stokes amplitude and undergoes a slow algebraic decay -g ' . In the latter regime, toward which the system always tends, self-similar oscillations whose number is proportional to g' occur.…”
Section: Introductionmentioning
confidence: 94%
“…(18). Equation (21) 3, =sech(r), 22 =exp(ivor)sech(r), (22) 82=sin(po/2)+ g b2 J p, j=1 (19) which corresponds physically to a frequency mismatch.…”
Section: IVmentioning
confidence: 99%
“…In later experiments by Duncan et al [16] a careful comparison between theory and experiment showed good agreement. Shortly after this work [16], Hilfer and Menyuk [17] carried out simulations which indicate that in the highly depleted regime the solutions of transient SRS equations always tend toward a self-similar solution. This result has been recovered by Menyuk et al [18,19] applying the inverse scattering transform method (ISM) to the transient SRS equations, see [12].…”
Section: Introductionmentioning
confidence: 99%